The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3092908
|View full text |Cite
|
Sign up to set email alerts
|

HCN polymers characterized by solid state NMR: Chains and sheets formed in the neat liquid

Abstract: Hydrogen cyanide polymerizes readily under a variety of conditions and significant prebiotic roles have been suggested for these polymers due to the abundance of HCN in universe. However, the structures of HCN polymers have been more speculative than grounded in experimental data. Here we show that 13 C and 15 N solid state NMR spectra of polymers formed in neat HCN are inconsistent with the previously proposed structures and suggest instead that the polymers are formed by simple monomer addition, first in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 35 publications
4
83
0
Order By: Relevance
“…Very recently Mamajanov and Herzfeld [28,29] using solid state 13 C and 15 N NMR spectra have investigated the chemical structure of the PHC prepared by a free radical and a base-catalyzed reaction and also obtained by heating the HCN tetramer. Unfortunately, the spectra reported by these authors are different from the solid state 13 C NMR CP-MAS reported in Fig.…”
Section: Chemical Structure Of the Black Insoluble Polymer Formed By mentioning
confidence: 99%
“…Very recently Mamajanov and Herzfeld [28,29] using solid state 13 C and 15 N NMR spectra have investigated the chemical structure of the PHC prepared by a free radical and a base-catalyzed reaction and also obtained by heating the HCN tetramer. Unfortunately, the spectra reported by these authors are different from the solid state 13 C NMR CP-MAS reported in Fig.…”
Section: Chemical Structure Of the Black Insoluble Polymer Formed By mentioning
confidence: 99%
“…Taken together, the results suggest that each HCN tetramer loses one HCN monomer per molecule upon polymerization. Figure 3 compares 13 C CPMAS spectra of DAMN, DAMN polymer, and conventional HCN polymer ͑prepared as described previously 6 ͒. In all cases, the narrow signals are due to crystalline DAMN and the broad signals are due to polymer.…”
Section: G Electrical Conductivity Measurementsmentioning
confidence: 99%
“…[1][2][3][4][5] One of most intriguing proposals, 2 based on observations of ␣-amino acids in polymer hydrolysates, suggests the formation of protopeptides by acid-base polymerization of the HCN trimer, aminomalononitrile. However, our previous NMR study 6 showed that protopeptide is not formed in the polymerization of neat HCN. On the other hand, the same study showed that crystalline HCN tetramer, diaminomaleonitrile ͑DAMN͒ ͓Figs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysis experiments of the polymers result in the observation of amino acids with particularly significant amounts of glycine and polycyclic nitrogenous compounds such as purines and imidazole derivatives (Supplementary Figure S1). 9,11,[24][25][26][27][28][29][30] Because of these properties, we investigated the AMN polymer as a candidate for a new generic coating method that may be particularly useful in biomedical applications such as cell culture tools, providing high cell attachment and surface coatings on implantable medical devices providing enhanced tissue integration.…”
Section: Introductionmentioning
confidence: 99%